Medico - botanical study of Yercaud hills in the eastern Ghats of Tamil Nadu, India - Parthipan, M (Medknow Publications & Media Pvt Ltd, 2011)
The study reports medicinal plant survey was conceded in Yercaud hills ranges of Eastern Ghats, Tamil Nadu, India. The study primarily based on field surveys conducted throughout the hills, where dwellers provided information on plant species used as medicine, plant parts used to prepare the remedies and ailments to which the remedies were prescribed. The study resulted about 48- plant species belonging to 45- genera and 29- families of medicinal plants related to folk medicine used by the local people. Among them the most common plants viz., Asparagus racemosus Willd., Cissus quadrangularis L., Gymnema sylvestre R. Br., Hemidesmus indicus (L.) R. Br., Justisia adhatoda L., Ocimum sanctum L., Phyllanthes amarus Schum. & Thonn., Piper nigrum L., Solanum nigrum L., Tinospora cordifolia (Thunb.) Miers, Tridax procumbens L. and Zingiber officinale Roscoe which are used in their daily life to cure various ailments.